2023
DOI: 10.1038/s41598-023-36406-8
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-driven controls on fluid and carbonate precipitation distributions in fractures

Abstract: Many challenges related to carbon-dioxide ($$\hbox {CO}_2$$ CO 2 ) sequestration in subsurface rock are linked to the injection of fluids through induced or existing fracture networks and how these fluids are altered through geochemical interactions. Here, we demonstrate that fluid mixing and carbonate mineral distributions in fractures are controlled by gravity-driven chemical dynamics. Using optical imaging and nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…From the concentration distributions (Figure 13e) of Case 11, although the inertial force is smaller, the lower part of the runlet is still straight due to the inertial force. Further, the upper part of the runlet is unstable in both cases but the wavelength in Case 11 is significantly shorter than that in the reference case, which is consistent with what is observed in laboratory experiments (Xu et al, 2023). Studies on confined laminar impinging slot-jet also reported that the size of a vortex increases with increasing Reynolds number (Sexton et al, 2018;Sivasamy et al, 2007).…”
Section: Influence Of Inertial Forcesupporting
confidence: 85%
See 1 more Smart Citation
“…From the concentration distributions (Figure 13e) of Case 11, although the inertial force is smaller, the lower part of the runlet is still straight due to the inertial force. Further, the upper part of the runlet is unstable in both cases but the wavelength in Case 11 is significantly shorter than that in the reference case, which is consistent with what is observed in laboratory experiments (Xu et al, 2023). Studies on confined laminar impinging slot-jet also reported that the size of a vortex increases with increasing Reynolds number (Sexton et al, 2018;Sivasamy et al, 2007).…”
Section: Influence Of Inertial Forcesupporting
confidence: 85%
“…The denser fluid (Fluid 1) also contained a dye (Brocresol green) to enable the imaging of fluid distributions, and a RaspberryPi spy camera was used for digital imaging. Readers are referred to Xu et al (2023) for additional experimental details.…”
Section: Experimental and Numerical Simulation Setupmentioning
confidence: 99%